Undermining Normalcy: A tentative introduction on the prospects of queer pedagogy - Altunpolat, Remzi (Feminist Asylum: A Journal of Critical Interventions, 2022)
Education is one of the building blocks of heteronormativity. It has a pivotal role in ensuring the continuity of gender hierarchy and the marginalization of alternative sexualities. Education processes the social reproduction of gendered bodies from childhood onwards by establishing a hierarchical model of differences among sexualities and sexual identities. In this respect it functions as factory of heterosexuality. In the school, heterosexuality is 'natural'; thus there is no requisite to talk about it. Curriculum, disciplinary regulations, teacher - student interactions, dress codes, supervision - control and many more practices, as well as school rituals and the physical space of the school function to the benefit of established heteronormative structures by enhancing gender differentiations.